Effect of Glass Powder on Physical and Mechanical Properties of Reactive Powder Concrete (RPC) - Ardiansyah, Ardiansyah; Sutandar, Erwin; Supriyadi, Asep (Fakultas Teknik Universitas Tanjungpura, 2024)
Glass waste is often dumped directly into the ground or rivers in large quantities, causing environmental pollution. To overcome this problem, glass waste can be processed into powder as a mixture in concrete. This research partially uses glass powder to replace silica fume in reactive powder concrete. This research uses experimental methods to test concrete's physical and mechanical properties. The research process includes making test specimens, analyzing materials, curing, testing slump, compressive strength, split tensile strength, and elasticity modulus. The results showed that the slump values ranged from 50-75 mm, with an average volume weight of 1.990,073 kg/m ³ - 2.149,228 kg/m ³. The average compressive strength values were in the range of 56,277 MPa